Immunologic Defense Mechanism in Human Milk - Ariyanto Harsono (Indonesian Pediatric Society, 1995)
Breast feeding has been intensively campained throughout the country in the last decade, which is thought to be responsible for the decline of the incidence of gastroenteritis. One of the most important advantages of breast feeding is the immunologic properties of breast milk. The importance of breast milk in the protection of many infections of the newly born infants, who are naturally immunologically deficient, is well-established. Breast milk contains humoral as well as cellular immunity components, each component has its elements although it is possible to describe the role of each components, it is generally thought that the protective properties of human milk against infections in neonates and young babies are the results of interactions of many factors rather than the effect of solely each factor. The role of humoral (immunoglobulins) and cellular (macrophages, lymphocytes, and other cellular elements) immunity of human milk, especially its protective properties, is discussed in this article.